«EDUCATIONAL ENGINEERING» IN THE CONTEXT OF THE IMPLEMENTATION OF THE CDIO IDEOLOGY - Alexandеr P. Isaev; Leonid V. Plotnikov (Moscow Polytechnic University, 2016)
Abstract. The article presents an educational project of the implementation of the main ideas of the CDIO worldwide initiative developed at the higher engineering school of Ural Federal University. A description of a new practical educational course and the authors' technology of educational engineering are presented. They are designed to prepare graduates to work in different stages of the life cycle of a technical system. The comparative analysis of the developed educational technologies and the technologies used by the other universities (Massachusetts Institute of Technology, The Franklin W. Olin College of Engineering, and Singapore Polytechnic) given in the article shows that our model of study engineering basically differs from the methods applied at the leading universities. The results of the application of educational engineering in the teaching process of engineering baccalaureate in Ural Federal University as well as the analysis of the resources necessary for widespread implementation of the developed innovations in educational process are presented in the article.